2023
DOI: 10.3390/diagnostics13061021
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Ruptured Hepatocellular Carcinoma: Computed Tomography-Based Assessment

Abstract: Spontaneously ruptured hepatocellular carcinoma (SRHCC) is an uncommon and life-threatening complication in patients with hepatocellular carcinoma (HCC). It is usually associated with chronic liver disease and has a poor prognosis with a high mortality rate during the acute phase. SRHCC can cause a severe and urgent condition of acute abdomen disease and requires a correct diagnosis to achieve adequate treatment. Clinical presentation is related to the presence of hemoperitoneum, and abdominal pain is the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 99 publications
(135 reference statements)
0
1
0
Order By: Relevance
“…Detection of focal lesions and haemorrhage is key to diagnosing an HCC rupture. 4 Iwasaki et al reported CT manifestations in 5 cases of an HCC rupture in the caudate lobe of the liver. 5 All cases showed exophytic tumours in the caudate lobe and high-attenuation haematomas in the lesser sac.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of focal lesions and haemorrhage is key to diagnosing an HCC rupture. 4 Iwasaki et al reported CT manifestations in 5 cases of an HCC rupture in the caudate lobe of the liver. 5 All cases showed exophytic tumours in the caudate lobe and high-attenuation haematomas in the lesser sac.…”
Section: Discussionmentioning
confidence: 99%
“… 10 This improvement is particularly attributed to the widespread recognition and utilization of therapeutic measures such as emergency or delayed partial hepatectomy and transcatheter arterial chemoembolization (TACE). 3 , 7 , 11 , 12 However, studies indicate that ALF accounts for more than half of the in-hospital mortality post emergency hepatectomy for SRHCC. 13 Furthermore, the incidence of liver failure following TACE can reach up to 12–34%.…”
Section: Introductionmentioning
confidence: 99%
“…Multiphasic computed tomography (CT) is the best imaging modality for diagnosing rHCC [12]. Hemoperitoneum, subcapsular hematoma, or active bleeding is typically seen.…”
Section: Introductionmentioning
confidence: 99%